2023
DOI: 10.3389/fpsyg.2023.1122986
|View full text |Cite
|
Sign up to set email alerts
|

Parental burnout and adolescents’ academic burnout: Roles of parental harsh discipline, psychological distress, and gender

Abstract: Parental burnout is an emerging hot issue in discussions about children’s mental health and development. However, little is known about the underlying psychological mechanisms of parental burnout on children’s academic burnout. To fill in this gap, we aim to examine the relationship between parental burnout and adolescents’ academic burnout, as well as the mediating effects of harsh discipline, adolescents’ psychological distress, and the moderating effect of gender. A sample of 871 junior high school students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Children ranged in age from 0 to 18, with the majority being typical between 0 and 6 years old. Two researchs study on parenting burnout in infants [ 30 , 34 ], five studies [ 16 , 18 , 29 , 33 , 51 ] on parenting burnout in parents of exceptional children, one study [ 48 ] on children with diabetes and one study on kids who needed ongoing pediatric outpatient care [ 32 ]. Seventeen research included both mothers and fathers, and nine studies [ 28 , 30 , 31 , 34 , 40 42 , 47 , 52 ] were conducted on a sample of just mothers from the general community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children ranged in age from 0 to 18, with the majority being typical between 0 and 6 years old. Two researchs study on parenting burnout in infants [ 30 , 34 ], five studies [ 16 , 18 , 29 , 33 , 51 ] on parenting burnout in parents of exceptional children, one study [ 48 ] on children with diabetes and one study on kids who needed ongoing pediatric outpatient care [ 32 ]. Seventeen research included both mothers and fathers, and nine studies [ 28 , 30 , 31 , 34 , 40 42 , 47 , 52 ] were conducted on a sample of just mothers from the general community.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in addition to affecting the parents themselves, parental burnout has serious repercussions on children by leading parents to be neglectful or even violent towards their offspring [13,14]. Parental burnout is also considered to be a risk factor for academic burnout and internal/external problems in children [15][16][17], which increases adolescents' levels of anxiety and loneliness, aggressive behavior, and depression, reducing adolescents' life satisfaction and mental health [18]. In the case of families, parenting burnout increases the frequency and intensity of spousal conflict [6], strains family relations and reduces the quality of life and life satisfaction of family members.…”
Section: Introductionmentioning
confidence: 99%
“…However, research has suggested that there is a correlation between maternal parenting burnout and psychological aggression. [37][38][39] From a biological perspective, stress can trigger and fuel anger, 40 while emotional and physical burnout may restrict executive resources that are available to curb negative behavior. 41 Mothers who are overworked or chronically exposed to parenting stress will fall into a state of parenting burnout, which can undermine their capacity to regulate negative parenting behaviors.…”
Section: The Chain-mediating Effect Of Maternal Parental Burnout and ...mentioning
confidence: 99%
“…Individual internal factors include factors such as professional commitment (Lian et al, 2006), coping styles (Shi et al, 2023), academic anxiety (Gao, 2023), loneliness (Gu et al, 2023), self-esteem (Yu et al, 2023), achievement motivation (Atik and Çelik, 2021), personality (Lee et al, 2017;Kong et al, 2021), positive psychological capital (Wang et al, 2021), psychological resilience (Gong et al, 2023), self-efficacy (Chen et al, 2023), and core self-evaluation (Dortaj, 2021). External environmental factors include stress (Watson et al, 2008;Gong et al, 2023;Shi et al, 2023), social support (Ye et al, 2021;Fu, 2023), parental education anxiety (Kai et al, 2022), parental supervision (Affuso et al, 2017), and parent-child attachment (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%